Combining possibly reciprocally dependent linguistic parameters in the quantitative assessment of aphasic speakers' grammatical output - Ruiter, Marina B.; Kolk, Herman H. J.; Rietveld, Toni. C. M.; Feddema, Ilse (Aphasiology, 2013)
Background: The grammatical output of aphasic speakers is often quantitatively analysed in order to establish an effect of treatment. In many methods of quantitative analysis both the number of utterances produced and (their) length are calculated. The difficulty is that these parameters may show a trade-off effect (i.e., may be inversely proportional to each other). That is, when the amount of information to be conveyed remains constant, an increase in the number of utterances may be compensated by a decrease in their length (and vice versa). As a result, a lack of increase-or even a decrease-in one of both outcome measures may be incorrectly interpreted as a lack of effect of treatment. Aims: The current study investigated whether combining the possibly reciprocal outcome measures percentage of utterances and (their) length into a single parameter increases the interpretability of the results obtained with a quantitative analysis of aphasic speakers' spontaneous speech. In the current study the procedure of combining two possibly reciprocal linguistic variables into one dependent measure is demonstrated for the elliptical repertoire. Ellipses are grammatically well formed but incomplete utterances (e.g., problem solved). Contrary to sentences, ellipses lack finiteness. As will be argued in this article, the procedure of combining possibly reciprocal outcome measures could be useful in order to investigate both the sentential and elliptical repertoire produced by aphasic speakers. Methods & Procedures: The possibly reciprocal outcome measures percentage of ellipses and mean length of ellipsis, which were used in the study of Ruiter, Kolk, and Rietveld ( 2010 ), were combined into a single parameter of elliptical style: percentage of words produced in ellipses (in comparison to words in sentences). The data obtained by Ruiter et al. ( 2010 ), who investigated the effect of a compensation therapy on the production of ellipses in 12 chronically agrammatic speakers of Dutch, were re-analysed with the new parameter. Outcomes & Results: The parameter percentage words produced in ellipses was not only able to reproduce the results obtained in the previous study, but also seems to be more sensitive: It could identify significant changes in elliptical style in more participants than the two possibly reciprocal parameters could independently. Conclusions: The data obtained in the current study may be of relevance to aphasia researchers and therapists as the new parameter provides them with a more sensitive measure to establish the effect of therapy on aphasic speakers' grammatical output.